Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

emma63

  • 2 years ago

What's the answer to 4(6z-1)-5(z+9)=6(z+1)

  • This Question is Closed
  1. Math2400
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    first you nee to distribute. know how to do that?

  2. Saumya.Gandhi
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    24z-4-5z-45=6z+6 ; 19z-6z=6+49 ; 13z= 55; z=55/13

  3. britbrat4290
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    z=55/13

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy